Home advantage in the Winter Olympics (1908-1998) - Balmer, N. J.; Nevill, A. M.; Williams, A. M. (Journal of Sports Sciences, 2001)
We obtained indices of home advantage, based on the medals won by competing nations, for each event held at the Winter Olympics from 1908 to 1998. These indices were designed to assess home advantage while controlling for nation strength, changes in the number of medals on offer and the performance of 'non-hosting' nations. Some evidence of home advantage was found in figure skating, freestyle skiing, ski jumping, alpine skiing and short track speed skating. In contrast, little or no home advantage was observed in ice hockey, Nordic combined, Nordic skiing, bobsled, luge, biathlon or speed skating. When all events were combined, a significant home advantage was observed (P = 0.029), although no significant differences in the extent of home advantage were found between events (P > 0.05). When events were grouped according to whether they were subjectively assessed by judges, significantly greater home advantage was observed in the subjectively assessed events (P = 0.037). This was a reflection of better home performances, suggesting that judges were scoring home competitors disproportionately higher than away competitors. Familiarity with local conditions was shown to have some effect, particularly in alpine skiing, although the bobsled and luge showed little or no advantage over other events. Regression analysis showed that the number of time zones and direction of travel produced no discernible trends or differences in performance.